Endoscopic Endonasal Focal Transclival-Medial Condylectomy Approach for Resection of a Foramen Magnum Meningioma: 2-Dimensional Operative Video. Issue 2 (11th June 2018) - Revuelta Barbero, Juan M; Montaser, Alaa S; Shahein, Mostafa; Beer-Furlan, André; Otto, Bradley A; Carrau, Ricardo L; Prevedello, Daniel M
Abstract: The endoscopic endonasal approach (EEA) provides direct access to foramen magnum meningiomas; however, it often requires extensive exposure including septal flap elevation with septum removal, complete sphenoidotomy, and panclivectomy. We present a case of a 54-yr-old-female with an incidental foramen magnum lesion followed up with serial imaging who presented 10 mo later with progressive neck discomfort and episodes of dizziness, with confirmed tumor progression and further brainstem compression. A focal transclival EEA with medial condylectomy was performed preserving the upper two-thirds of the clivus, the nasal septum, and the sphenoid sinus. Gross total removal of a meningioma WHO Grade-1 was achieved with dura resection on the majority of the tumor (Simpson 2). Closure was achieved with a random pedicled inverted V nasaopharyngeal flap. There were no complications, all symptoms improved, and no recurrence was seen in 12 mo of follow-up. IRB approval was neither required nor saught for this single case report. The patient gave informed consent.